List of IMF Member Countries with Delays in Completion of Article IV Consultations Over 18 Months or Mandatory Financial Stability Assessment Over 18 Months. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2015)
This Staff Report Lists IMF Member Countries with Delays in Completion of Article IV Consultations over 18 Months or Mandatory Financial Stability Assessment over 18 Months, prepared by IMF staff and completed on January 28, 2015.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Consultation; IMF Member Countries With Delay; IMF Staff; Month; PP; Argentina